2022
DOI: 10.1007/s00044-022-03009-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioactivity evaluation of pachymic acid derivatives as potential cytotoxic agents

Abstract: Pachymic acid, a well-known natural lanostane-type triterpenoid, exhibits various pharmacological properties. In this study, 18 derivatives of pachymic acid were synthesized by modifying their molecular structures and evaluated for their anticancer activity against two human cancer cell lines using the CCK-8 assay. Structure-activity relationship studies according to the in vitro cytotoxicity unexpectedly found one promising derivative A17 (namely tumulosic acid, also found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The introduction of a hydroxy group at C-2 rendered forpinioside C ( 2 ) inactive in antimicrobial assays compared to forpinioside B ( 1 ), however; both compounds were not active in the cytotoxicity assay. Recent structure–activity relationship (SAR) studies have indicated a key role played by the hydroxy group at C-3 in cytotoxic effects of lanostane triterpenoids [ 23 , 36 ]. According to a study by Wang et al (2023) [ 36 ], synthetic derivatives of pachymic acid demonstrated moderate to high potency against cancer cells in the presence of a 3-OH group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The introduction of a hydroxy group at C-2 rendered forpinioside C ( 2 ) inactive in antimicrobial assays compared to forpinioside B ( 1 ), however; both compounds were not active in the cytotoxicity assay. Recent structure–activity relationship (SAR) studies have indicated a key role played by the hydroxy group at C-3 in cytotoxic effects of lanostane triterpenoids [ 23 , 36 ]. According to a study by Wang et al (2023) [ 36 ], synthetic derivatives of pachymic acid demonstrated moderate to high potency against cancer cells in the presence of a 3-OH group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent structure–activity relationship (SAR) studies have indicated a key role played by the hydroxy group at C-3 in cytotoxic effects of lanostane triterpenoids [ 23 , 36 ]. According to a study by Wang et al (2023) [ 36 ], synthetic derivatives of pachymic acid demonstrated moderate to high potency against cancer cells in the presence of a 3-OH group. Notably, hydrolysis of the C3-acetoxy group in pachymic acid to tumulosic acid increased the activity of the compound compared to the positive control (cisplatin), in some instances [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations